THE ROLE OF ARTIFICIAL INTELLIGENCE IN OVERCOMING GLOBAL ECONOMIC UNCERTAINTY - Loso Judijanto; Bahrun Thalib; Megandhi Gusti Wardhana; Al-Amin (CV. Adiba Aisha Amira, 2024)
Artificial Intelligence (AI) is rapidly changing the global economic landscape, promising greater operational efficiency, product innovation and solutions to long-term economic challenges. However, the broad impact of this technology on the economy varies widely and raises questions about its future implications for labor, economic equality, and global market competition. The study conducted in this research uses the literature research method. The results show that AI plays a key role in advancing innovation, increasing productivity, and addressing some pressing economic challenges such as energy efficiency and climate change. However, it also identifies significant risks in terms of job displacement, increased inequality, and concentration of market power in the hands of large technology companies.